Optogenetic modulation of descending prefrontocortical inputs to the dorsal raphe bidirectionally bias socioaffective choices after social defeat - Challis, Collin; Beck, Sheryl G.; Berton, Olivier (Frontiers in Behavioral Neuroscience, 2014)
It has been well established that modulating serotonin (5-HT) levels in humans and animals affects perception and response to social threats, however the circuit mechanisms that control 5-HT output during social interaction are not well understood. A better understanding of these systems could provide groundwork for more precise and efficient therapeutic interventions. Here we examined the organization and plasticity of microcircuits implicated in top-down control of 5-HT neurons in the dorsal raphe nucleus (DRN) by excitatory inputs from the ventromedial prefrontal cortex (vmPFC) and their role in social approach-avoidance decisions. We did this in the context of a social defeat model that induces a long lasting form of social aversion that is reversible by antidepressants. We first used viral tracing and Cre-dependent genetic identification of vmPFC glutamatergic synapses in the DRN to determine their topographic distribution in relation to 5-HT and GABAergic subregions and found that excitatory vmPFC projections primarily localized to GABA-rich areas of the DRN. We then used optogenetics in combination with cFos mapping and slice electrophysiology to establish the functional effects of repeatedly driving vmPFC inputs in DRN. We provide the first direct evidence that vmPFC axons drive synaptic activity and immediate early gene expression in genetically identified DRN GABA neurons through an AMPA receptor-dependent mechanism. In contrast, we did not detect vmPFC-driven synaptic activity in 5-HT neurons and cFos induction in 5-HT neurons was limited. Finally we show that optogenetically increasing or decreasing excitatory vmPFC input to the DRN during sensory exposure to an aggressor’s cues enhances or diminishes avoidance bias, respectively. These results clarify the functional organization of vmPFC-DRN pathways and identify GABAergic neurons as a key cellular element filtering top-down vmPFC influences on affect-regulating 5-HT output.